2016
DOI: 10.1016/j.appet.2015.08.009
|View full text |Cite
|
Sign up to set email alerts
|

Greater anterior cingulate activation and connectivity in response to visual and auditory high-calorie food cues in binge eating: Preliminary findings

Abstract: Obese individuals show altered neural responses to high-calorie food cues. Individuals with binge eating [BE], who exhibit heightened impulsivity and emotionality, may show a related but distinct pattern of irregular neural responses. However, few neuroimaging studies have compared BE and non-BE groups. To examine neural responses to food cues in BE, 10 women with BE and 10 women without BE (non-BE) who were matched for obesity (5 obese and 5 lean in each group) underwent fMRI scanning during presentation of v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
45
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(50 citation statements)
references
References 59 publications
2
45
0
3
Order By: Relevance
“…This network is essential for the processing of personally salient stimuli and involved in emotional arousal, food, and reward processing (DelParigi et al, ) and might therefore play an essential role in the psychopathology of BTE disorders. Furthermore, the ACC has been consistently found to be associated with both BED and BN (Geliebter, Benson, Pantazatos, Hirsch, & Carnell, ; Schienle, Schäfer, Hermann, & Vaitl, ; Seitz et al, ). Especially the dorsal part of the ACC has been described as an important hub of the SN (Seeley et al, ), our results therefore suggest alterations in salience processing circuits as a possible candidate for an underlying trait marker of BTE disorders.…”
Section: Discussionmentioning
confidence: 99%
“…This network is essential for the processing of personally salient stimuli and involved in emotional arousal, food, and reward processing (DelParigi et al, ) and might therefore play an essential role in the psychopathology of BTE disorders. Furthermore, the ACC has been consistently found to be associated with both BED and BN (Geliebter, Benson, Pantazatos, Hirsch, & Carnell, ; Schienle, Schäfer, Hermann, & Vaitl, ; Seitz et al, ). Especially the dorsal part of the ACC has been described as an important hub of the SN (Seeley et al, ), our results therefore suggest alterations in salience processing circuits as a possible candidate for an underlying trait marker of BTE disorders.…”
Section: Discussionmentioning
confidence: 99%
“…Obese women showed higher functional connectivity between the midbrain/VTA and cerebellar hemispheres when they were exposed to highly caloric food cues (Carnell et al, 2014). In a recent study from the same lab, binge eaters exhibited greater functional connectivity between the cerebellum and dorsal ACC during the presentation of food-related cues (Geliebter et al, 2016). Intriguingly, there is an overlap in the fMRI signal evoked by cocaine and food-related cues in the cerebellum, which suggests a general role of this region in the processing of conditioned reinforcing cues in people suffering from compulsive-like disorders (Tomasi et al, 2015).…”
Section: The Cerebellum In Cravingmentioning
confidence: 96%
“…Although fewer neuroimaging studies exist for BED, a review of the research suggests that individuals with BED exhibit altered responses found in corticostriatal circuitry which are related to processing motivation/reward and impulsivity (28). Specifically, individuals with BED show increased activity in the dorsal anterior cingulate cortex in response to high calorie food cues compared to those without BED (29), suggesting or contributing to loss of control over the consumption of these foods. Adults with OW/OB and BED show less activity in the prefrontal cortex (i.e.…”
Section: Brief Overview Of Neurocognitive Deficits In Eating and Weigmentioning
confidence: 99%